NOISE IN LARGE PRODUCTION ENTERPRISES, ITS IMPACT ON THE HEALTH OF WORKERS AND METHODS OF COMBATING NOISE - H. Pakhirdinov; A.Normirzayev; M. Toragulov (ANTIS PUBLISHER, 2024)
Industrial production is one of the main areas of economic development of any country, so it is worth saying that large factories play a very important role in achieving high productivity. Large production enterprises are important in meeting the demands and needs of society